2021
DOI: 10.3390/plants10102103
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Giant Hogweed Invasion Contributes to the Structural Changes of Soil Nematofauna

Abstract: Heracleum mantegazzianum (giant hogweed) is the largest central European forb, naturalized or invasive in many European countries. The impacts of its colonization of native habitats on soil mesofauna groups are unfortunately obscure. This study assessed the effect of giant hogweed invasion on the communities of plants and soil nematodes in the riparian habitat. We found that invasion by H. mantegazzianum increased soil pH, decreased carbon and nitrogen content, reduced the number and coverage of the native pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Renčo, Jurová, Gömöryová and Čerevková, 2021 [186] Soil yeast communities Under H. sosnowskyi were less ascomycetes Candida vartiovaarae, Wickerhamomyces anomalus, although more yeast-like fungi with high hydrolytic activity:…”
Section: Hmmentioning
confidence: 96%
See 1 more Smart Citation
“…Renčo, Jurová, Gömöryová and Čerevková, 2021 [186] Soil yeast communities Under H. sosnowskyi were less ascomycetes Candida vartiovaarae, Wickerhamomyces anomalus, although more yeast-like fungi with high hydrolytic activity:…”
Section: Hmmentioning
confidence: 96%
“…Near H. sosnowskyi in an abandoned land and road-side slope were more bacterivorous, fewer fungivores, and plant parasites belonging to nematodes [184]. This type of research has been continued for many years, bringing new information to applied science [186,187].…”
Section: Biochemistry Of Invasive Caucasian Hogweedsmentioning
confidence: 99%
“…Although the main competitive characteristic of giant hogweed is to shade lower-growing species, Jandová et al [158] also pointed out that plants of this species can also release allelochemicals into the soil through their root system. It can also be assumed that these compounds are toxic to nematodes and other soil organisms [12]. Renčo et al [12] reported that the average number of nematode species at infested sites was up to 20% lower than the diversity of nematode species at uninfested sites.…”
Section: Impact On Biodiversity-evidence From the Broader European Te...mentioning
confidence: 99%
“…It can also be assumed that these compounds are toxic to nematodes and other soil organisms [12]. Renčo et al [12] reported that the average number of nematode species at infested sites was up to 20% lower than the diversity of nematode species at uninfested sites. The same authors also found that giant hogweed invasion increased soil pH from 6.23 to 7.20 and decreased soil carbon and nitrogen content by 24% and 31%, respectively, on riverbanks in the eastern part of Slovakia.…”
Section: Impact On Biodiversity-evidence From the Broader European Te...mentioning
confidence: 99%
See 1 more Smart Citation